2018
DOI: 10.1016/j.cub.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Encoding of the Visual Field in the Mouse Retina

Abstract: Stimulus characteristics of the mouse's visual field differ above and below the skyline. Here, we show for the first time that retinal ganglion cells (RGCs), the output neurons of the retina, gradually change their functional properties along the ventral-dorsal axis to allow better representation of the different stimulus characteristics. We conducted two-photon targeted recordings of transient-Offα-RGCs and found that they gradually became more sustained along the ventral-dorsal axis, revealing >5-fold-longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 66 publications
6
85
3
Order By: Relevance
“…Sensory neurons often display an ordered spatial arrangement that enhances the encoding of specific features on different sides of natural borders in the visual field (for example, [1][2][3]). In central visual areas, one prominent natural border is formed by the confluence of information from the two eyes, the monocular-binocular border [4].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory neurons often display an ordered spatial arrangement that enhances the encoding of specific features on different sides of natural borders in the visual field (for example, [1][2][3]). In central visual areas, one prominent natural border is formed by the confluence of information from the two eyes, the monocular-binocular border [4].…”
Section: Discussionmentioning
confidence: 99%
“…The retina was extracted and dissected in oxygenated Ames medium (Sigma, St. Louis, MO, USA) under dim red and infrared light. The isolated retina (dorsal part) was then mounted on a 0.22 mm membrane filter (Millipore) with a pre-cut window to allow light to reach the retina and put under a two-photon microscope (Bruker, Billerica, MA, USA) equipped with a Mai-Tai laser (Spectra-physics, Santa Clara, CA, USA) as previously described (Warwick et al, 2018). GFP cells were targeted for recordings with the laser set to 920 nm to minimally activate photoreceptors, and using a 60x water-immersion objective (Olympus, Tokyo, Japan).…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…One obvious question, therefore, is do dorsally located and ventrally located retinal neurons do exactly the same job, even though they tend to analyse different parts of the external world? A new study by Warwick et al [1], reported in this issue of Current Biology, reveals an unexpected division of labor among retinal ganglion cells of the same type depending on retinal location, which may reflect the different behavioral requirements.…”
mentioning
confidence: 91%